Assessment of the Social Infrastructure of the University as a Factor of its International Competitiveness - ROMANOVA, Irina Matveevna; NOSKOVA, Elena Viktorovna; TROTSENKO, Anastasiya Nikolaevna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
It is noted in the article that new principles of educational activities suppose interaction dynamics of all university structures, and at the same time, the social infrastructure plays an important role, as it is the main factor in increasing international competitiveness of the university. The main objective of the study is to identify factors of international competitiveness of universities and to determine a role of the social infrastructure among these factors, prove that a degree of importance of the social infrastructure elements of universities depends on the target audience composition of students. Within the framework of this study main factors of international competitiveness of universities were identified: qualification level of academic teaching staff, integration level of the university into international educational space, development level of material and technical base, which provides the learning process, development level of the social infrastructure of the university, level of library funds condition, integration level of the university with the business community, integration level of the university with research structures, including international ones, compliance of a proposed range of educational services with the needs of domestic and international markets, performance of research work of the university, and the role of social infrastructure among these factors is determined. Constituent elements of the social infrastructure of universities (housing and utilities, catering and trade, consumer services, culture and leisure, sports and recreation, communications) are highlighted, their importance for the Russian and Chinese students and the degree of satisfaction are evaluated.
Keywords: social infrastructure; competitiveness factors; competitiveness of the university; satisfaction